High-power bolt friction joint structure

By implementing a high-strength bolt friction bonding structure with controlled gaps and chemical conversion coatings on the joint surfaces, the issue of slip coefficient decrease after corrosion is addressed, resulting in improved structural integrity and corrosion resistance.

JP2025062893APending Publication Date: 2025-04-15NIPPON STEEL CORPORATION
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023172254
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-03
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In high-strength bolt friction bonding structures, gaps formed around the bolts during tightening lead to a decrease in the slip coefficient after corrosion, which has not been effectively addressed by existing technologies.

Method used

A high-strength bolt friction bonding structure where plated steel materials are frictionally joined using high-strength bolts, nuts, and washers, with a chemical conversion coating on the joint surfaces and controlled gaps between the steel surfaces, specifically maintaining a gap of 310 μm or less at a distance of 5 cm from the bolt hole edge.

Benefits of technology

This configuration effectively suppresses the drop in the slip coefficient after corrosion, enhancing the structural integrity and corrosion resistance of the high-strength bolt friction bonding structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025062893000001_ABST
    Figure 2025062893000001_ABST
Patent Text Reader

Abstract

To suppress the lowering of a slide coefficient after the corrosion of a high-power bolt friction joint structure to which surface treatment is applied.SOLUTION: A high-power bolt friction joint structure 10 has a plating part at a surface, and friction-joins a first plated steel material 20, a second plated steel material 26 and a third plated steel material 32 in which a first bolt hole 24, a second bolt hole 28 and a third bolt hole 30 are formed, respectively, by using a high-power bolt 34, a nut 36 and a washer 38, and a chemical conversion coating is formed at least at one plated-material joint face (a first superimposition face 22A, a first superimposition face 22B, a second superimposition face 26A and a third superimposition face 30A) of the joint part by surface treatment for enhancing a slide coefficient, and in the joint part, a clearance G between surfaces of the steel materials which oppose each other is equal to or smaller than 310 μm in a position in which a separation distance X from a bolt hole edge E along a radial direction of the bolt hole is 5 cm.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a high strength bolt friction joint structure. [Background technology]

[0002] Conventionally, there is known a high-strength bolt friction joint structure in which a plurality of plated steel materials are frictionally joined by a high-strength bolt, a nut, and a washer, as in Patent Document 1. In the high-strength bolt friction joint structure of Patent Document 1, in order to improve the slip coefficient, a zinc phosphate coating formed by zinc phosphate treatment as a surface treatment is provided as an anti-rust coating on the joining surfaces of the steel sheets.

[0003] In addition, Patent Document 2 does not disclose a high-strength bolt friction joint structure itself, but discloses a phosphate conversion treatment applied only to the surface of a "screw member" consisting of a high-strength bolt, a nut, and a washer. Patent Document 2 states that the load-bearing, corrosion resistance, and heat resistance properties of the screw member can be improved by the phosphate conversion treatment. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2020-165187 A [Patent Document 2] Japanese Patent Publication No. 153783 / 1983 Summary of the Invention [Problem to be solved by the invention]

[0005] In a joint of a high-strength bolt friction joint structure, a gap is formed around the high-strength bolt between overlapping steel materials due to bolt tightening, and the gap becomes larger as it moves away from the high-strength bolt. Here, the present inventors have obtained a new finding that by controlling the gap of the joint during construction, it is possible to suppress the decrease in the slip coefficient after corrosion (in other words, after construction) in a high-strength bolt friction joint structure that has been subjected to a surface treatment.

[0006] In this regard, Patent Documents 1 and 2 do not consider technology for suppressing the decrease in the slip coefficient after corrosion in a surface-treated high-strength bolt friction joint structure by managing the gap at the joint during construction. [Means for solving the problem]

[0007] The present disclosure has been made in consideration of the above, and provides a high-strength bolt friction joint structure that can suppress a decrease in the slip coefficient after corrosion in a high-strength bolt friction joint structure that has been subjected to a surface treatment.

[0008] The high-strength bolt friction joint structure of the present disclosure is a high-strength bolt friction joint structure in which a plurality of plated steel materials having plated portions on their surfaces and bolt holes formed therein are frictionally joined by high-strength bolts, nuts, and washers, wherein a chemical coating is formed on the joining surface of at least one of the plated steel materials at the joint by a surface treatment for increasing the slip coefficient, and the gap between opposing surfaces of the plated steel materials at the joint at a position 5 cm away from the bolt hole edge in the radial direction of the bolt hole is 310 μm or less. Effect of the Invention

[0009] According to the present disclosure, it is possible to provide a high-strength bolt friction joint structure that can suppress a decrease in the slip coefficient after corrosion in a high-strength bolt friction joint structure that has been subjected to a surface treatment. [Brief description of the drawings]

[0010] [Figure 1]1 is a plan view of a high-strength bolt friction joint structure according to an embodiment of the present disclosure, viewed from the head side of the high-strength bolt. FIG. [Diagram 2] FIG. 1 is a side view of a high-strength bolt friction joint structure according to an embodiment of the present disclosure. [Diagram 3] FIG. 4 is a partially enlarged view illustrating a gap formed in an overlapping portion of the high-strength bolt friction joint structure according to the embodiment. [Figure 4] 3 is an enlarged view of part A in FIG. 2 illustrating a gap that occurs in the high-strength bolt friction joint structure according to the present embodiment. FIG. [Diagram 5] 13 is a graph illustrating the relationship between the distance from the bolt hole and the gap in the high-strength bolt friction joint structure according to the embodiment in the cases of "no corrosion" and "corrosion". [Figure 6] FIG. 6(A) is a photograph of the high-strength bolt friction joint structure of Test Example 1 of the embodiment, which was subjected to a 48-cycle accelerated corrosion test, viewed from the upper side; FIG. 6(B) is a photograph of the high-strength bolt friction joint structure of Test Example 1, viewed from the head side of the high-strength bolt; and FIG. 6(C) is a photograph of the high-strength bolt friction joint structure of Test Example 1, viewed from the lower side. [Figure 7] FIG. 7(A) is a cross-sectional SEM image taken by cutting the high-strength bolt friction joint structure of Test Example 1 of the embodiment with 0 cycles of “no corrosion” at the same position as the position of line 7-7 in FIG. 6(B), and FIG. 7(B) is a cross-sectional SEM image taken by cutting the high-strength bolt friction joint structure of Test Example 1 of the embodiment with 48 cycles of accelerated corrosion testing at the position of line 7-7 in FIG. 6(B). [Figure 8] 13 is a graph illustrating normal distributions showing the relationship between the slip coefficient and the probability density before and after corrosion of the high-strength bolt friction joint structure according to the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present embodiment will be described below. In the following description of the drawings, the same or similar parts are given the same or similar symbols. However, the relationship between thickness and planar dimensions in the drawings, the thickness ratio of each device and each member, etc. are different from the actual ones. Therefore, the specific thickness and dimensions should be determined by taking into consideration the following description. In addition, there are parts whose dimensional relationships and ratios differ between the drawings. In addition, unless otherwise specified in the specification, the number of each component of the present disclosure is not limited to one, and there may be more than one.

[0012] <High-strength bolt friction joint structure> A high-strength bolt friction joint structure 10 according to this embodiment will be described with reference to Figures 1 to 4. As shown in Figures 1 and 2, the high-strength bolt friction joint structure 10 according to this embodiment is a high-strength bolt friction joint structure in which a first plated steel material 20, a second plated steel material 26, and a third plated steel material 30 are frictionally joined by a high-strength bolt 34, a nut 36, and a washer 38.

[0013] (Plated steel) The first plated steel material 20, the second plated steel material 26, and the third plated steel material 30 correspond to the plurality of plated steel materials of the present disclosure. A plated portion is formed on the surface of each of the first plated steel material 20, the second plated steel material 26, and the third plated steel material 30. Plated steel materials are advantageous in terms of improving rust resistance.

[0014] 3 and 4, a first bolt hole 24 is formed in the first plated steel material 20. A second bolt hole 28 is formed in the second plated steel material 26. A third bolt hole 32 is formed in the third plated steel material 30. The shanks of high-strength bolts 34 pass through the first bolt holes 24, the second bolt holes 28 and the third bolt holes 32.

[0015] 1 and 2, in this embodiment, a high-strength bolt friction joint structure 10 has, as plated steel materials, a pair of first plated steel materials 20, a set of plated steel materials consisting of a second plated steel material 26 and a third plated steel material 30 sandwiching the pair of first plated steel materials 20, and a high-strength bolt 34. Note that, although the number of plated steel materials in this embodiment is four, this is not limited to this in the present disclosure, and the number of plated steel materials is two or more and is arbitrary. Each plated steel material in this embodiment will be specifically described below.

[0016] (First Plated Steel) The plate-shaped portion 22 of the first plated steel material 20 extends along the longitudinal direction L, as shown in Figures 1 and 2. The plate-shaped portion 22 of the first plated steel material 20 has a constant width along a width direction W perpendicular to the longitudinal direction L in Figure 1. The plate-shaped portion 22 of the first plated steel material 20 has a constant thickness along a thickness direction T in the up-down direction, as shown in Figure 2.

[0017] In the first plated steel material 20, a plurality of bolt holes are formed on the end 22E side in the longitudinal direction L of the plate-shaped portion 22, in portions that overlap with the second plated steel material 26 and the third plated steel material 30 in the thickness direction T. The end 22E is located in the center in the left-right direction in Figures 1 and 2.

[0018] In this embodiment, in the first plated steel material 20 on the left side in Fig. 1, two first bolt holes 24 are arranged in a portion of the plate-shaped portion 22 that overlaps with the second plated steel material 26 and the third plated steel material 30. In addition, in the first plated steel material 20 on the right side in Fig. 1, one first bolt hole 24 is arranged in a portion of the plate-shaped portion 22 that overlaps with the second plated steel material 26 and the third plated steel material 30. In the present disclosure, the number of bolt holes can be set arbitrarily to one or more.

[0019] 1 and 2, the pair of first plated steel materials 20 are connected to the second plated steel material 26 and the third plated steel material 30 by high-strength bolts 34 with the ends 22E of the plate-like portions 22 facing each other. Note that the high-strength bolts 34 used in this embodiment are high-strength hexagonal bolts, but the shape of the high-strength bolts of the present disclosure is not limited to hexagonal bolts and may be, for example, a torsion type. Also, in the present disclosure, the shapes of the nuts and washers can be appropriately changed.

[0020] The first plated steel material 20 has a base material and a plating layer as a plating portion. Specifically, for example, a plated steel sheet having a thickness of about 9.0 mm can be used as the first plated steel material 20 of this embodiment. Note that in the present disclosure, the thickness of the plated steel material can be changed as appropriate. The plating layer is formed to a predetermined thickness on the surface of the base material by applying a plating treatment such as an immersion method to the surface of the base material in a predetermined amount of adhesion.

[0021] (Second-Plated Steel) The second plated steel material 26 can be a plated steel material similar to the first plated steel material 20. In the present embodiment, as shown in Figures 1 and 2, the thickness of the second plated steel material 26 is illustrated as being thinner than the thickness of the first plated steel material 20, but in the present disclosure, the respective thicknesses can be changed as appropriate. As the second plated steel material 26, for example, a pre-plated steel sheet having a thickness of 0.8 mm can be used.

[0022] In this embodiment, three second bolt holes 28 are formed in the portion where the second plated steel material 26 overlaps with the plate-shaped portion 22 of the first plated steel material 20 in the thickness direction T. The second plated steel material 26 is joined to the plate-shaped portion 22 by high-strength bolts 34 in a state where it overlaps with the lower plate surface of the plate-shaped portion 22 in FIG. 2. The second plated steel material 26 also has a base material and a plating layer. The base material and plating layer of the second plated steel material 26 are similar to the base material and plating layer of the first plated steel material 20, so a duplicated explanation will be omitted.

[0023] (Third-Plated Steel) 1 and 2, the third plated steel material 30 is a plated steel material similar to the second plated steel material 26. In this embodiment, the shape of the third plated steel material 30 is the same as that of the second plated steel material 26. Note that in the present disclosure, the shape of the third plated steel material may be different from that of the second plated steel material.

[0024] In this embodiment, three third bolt holes 32 are formed in the portion where the third plated steel material 30 overlaps with the plate-shaped portion 22 of the first plated steel material 20 in the thickness direction T. The third plated steel material 30 is joined to the plate-shaped portion 22 by high-strength bolts 34 in a state where it overlaps with the upper plate surface of the plate-shaped portion 22 in FIG. 2. The third plated steel material 30 also has a base material and a plating layer. The base material and plating layer of the third plated steel material 30 are similar to the base material and plating layer of the first plated steel material 20, so a duplicated explanation will be omitted.

[0025] (High strength bolts, nuts, washers) The high-strength bolt 34 passes through the first bolt hole 24 in the first plated steel material 20, the second bolt hole 28 in the second plated steel material 26, and the third bolt hole 32 in the third plated steel material 30. The tip of the shaft of the high-strength bolt 34 is screwed into a nut 36. Washers 38 are respectively disposed between the head of the high-strength bolt 34 and the second plated steel material 26, and between the nut 36 and the third plated steel material 30.

[0026] (Surface treatment) The joining surfaces of the plate-shaped portion 22 of the first plated steel material 20 and the second plated steel material 26 and the third plated steel material 30, in other words, the overlapping surfaces, are subjected to a phosphate treatment as the surface treatment of the present disclosure. In this embodiment, when the plate-shaped portion 22 of the first plated steel material 20 and the second plated steel material 26 and the third plated steel material 30 are friction-joined, the plate surface of the first plated steel material 20 at the portion where the plate-shaped portion 22 of the first plated steel material 20 and the second plated steel material 26 overlap is referred to as a first overlapping surface 22A. Also, the plate surface of the second plated steel material 26 at the portion where the plate-shaped portion 22 of the first plated steel material 20 and the second plated steel material 26 overlap is referred to as a second overlapping surface 26A.

[0027] Additionally, the plate surface of the plate-shaped portion 22 of the first plated steel material 20 at the portion where the plate-shaped portion 22 of the first plated steel material 20 and the third plated steel material 30 overlap is referred to as a first overlapping surface 22B. Additionally, the plate surface of the third plated steel material 30 at the portion where the plate-shaped portion 22 of the first plated steel material 20 and the third plated steel material 30 overlap is referred to as a third overlapping surface 30A.

[0028] In this embodiment, a chemical conversion coating is formed by surface treatment to increase the slip coefficient on the joint surfaces of all plated steel materials in the joint of the high-strength bolt friction joint structure 10. Specifically, a first chemical conversion coating 23 as the chemical conversion coating of the present disclosure is disposed on the joint surfaces (first overlapping surface 22A, first overlapping surface 22B) of the first plated steel material 20. Also, a second chemical conversion coating 29 as the chemical conversion coating of the present disclosure is disposed on the joint surface (second overlapping surface 26A) of the second plated steel material 26.

[0029] Further, a third chemical conversion coating 33 as the chemical conversion coating of the present disclosure is disposed on the joining surface (third overlapping surface 30A) of the third plated steel material 30. In the present disclosure, it is sufficient that a chemical conversion coating is formed by surface treatment on the joining surface of at least one plated steel material in the joint.

[0030] More specifically, in this embodiment, the surface treatment is a zinc phosphate treatment. A zinc phosphate coating is formed by the zinc phosphate treatment. The zinc phosphate treatment can be performed, for example, by carrying a plated steel sheet with bolt holes formed therein to a construction site, and then applying a solution containing zinc phosphate to the surface of the plated steel sheet at the construction site using a spray, a brush, or the like. After a zinc phosphate coating is formed on the surface by a predetermined process such as application of the solution and drying treatment, the plated steel sheets may be friction-joined with a high-strength bolt.

[0031] In the present disclosure, the surface treatment is not limited to zinc phosphate treatment. For example, the surface treatment may include any one of zinc phosphate treatment, blast treatment of the plated portion, and coating treatment of inorganic zinc-rich paint. In addition, in the present disclosure, the surface treatment may be treatment other than zinc phosphate treatment, blast treatment of the plated portion, and coating treatment of inorganic zinc-rich paint.

[0032] The zinc phosphate coating on the joint surface of the high-strength bolt friction joint 10 is sheared by the sliding acting on the steel material. In other words, cohesive failure of the zinc phosphate coating occurs on the friction surface. The magnitude of the inherent slip resistance of the friction joint is determined by the cohesive failure of the zinc phosphate coating.

[0033] For example, a phosphate species capable of forming a normal crystalline zinc phosphate coating is used for the phosphating of the first plated steel material 20. The crystalline zinc phosphate coating may contain a mixture of metal salts or metals such as nickel (Ni) phosphate, manganese (Mn), magnesium (Mg), etc.

[0034] Phosphate treatment can be carried out by reactive treatment, coating treatment, electrolytic treatment, or other methods. For example, reactive phosphating is carried out by subjecting the first plated steel material 20 to a predetermined plating treatment, followed by the steps of phosphate pretreatment such as surface conditioning, phosphate treatment, rinsing, and drying. In the phosphate pretreatment, for example, an aqueous zinc phosphate solution or a titanium (Ti) colloidal solution is used. The phosphate pretreatment acts as a precipitation site for phosphate crystals, and is carried out to form a dense coating.

[0035] In this embodiment, the amount of zinc phosphate in the zinc phosphate coating as the chemical conversion coating is 1.0 g / m 2 More than 5.0g / m 2 The amount of zinc phosphate applied is 1.0 g / m 2 If the amount of zinc phosphate applied is less than 5.0 g / m, the amount of zinc phosphate applied will be insufficient, and as a result, there is a concern that the joint surface will be susceptible to corrosion. 2If the amount of zinc phosphate exceeds 1.0 g / m, the amount of zinc phosphate increases, resulting in a larger gap between the plated steel sheets at the joint and an easier intrusion of water, which may cause rust liquid to leak out and impair the appearance. 2 More than 5.0g / m 2 The value is not limited to the following and can be set arbitrarily.

[0036] (Method for measuring the amount of zinc phosphate attached) The amount of zinc phosphate attached may be measured, for example, by fluorescent X-ray analysis. Fluorescent X-ray analysis is a method for measuring the amount of elements in a substance to be measured by utilizing the intensity of specific X-rays generated when X-rays are irradiated onto the substance to be measured.

[0037] For example, the surface to be measured that has been treated with zinc phosphate can be subjected to fluorescent X-ray analysis to measure the intensity of the specific X-rays of phosphorus (P), and the amount of the element can be estimated by comparing the measured intensity with a calibration curve created in advance. Also, for example, a test piece with zinc phosphate attached can be taken from the high-strength bolt friction joint structure 10, and the amount of zinc phosphate attached can be determined by a gravimetric method in which the zinc phosphate coating is dissolved with ammonium chromate or the like. Also, for example, rust fluid that has flowed out from near the high-strength bolt friction joint can be taken and subjected to fluorescent X-ray analysis, and if P is confirmed, the use of zinc phosphate treatment can be approved.

[0038] (Formation of a conversion coating on the inner surface of the bolt hole) 1, in this embodiment, three bolt holes are formed, the first bolt hole 24, the second bolt hole 28 and the third bolt hole 32, through which three high-strength bolts 34 pass respectively. The inner surfaces of the first bolt hole 24, the second bolt hole 28 and the third bolt hole 32 do not function as joining surfaces where the plated steel sheet surfaces are overlapped with each other.

[0039] However, in this embodiment, a first chemical conversion coating 23 is disposed on the inner surface of a first bolt hole 24 in the first plated steel material 20. Furthermore, a second chemical conversion coating 29 is disposed on the inner surface of a second bolt hole 28 in the second plated steel material 26. Furthermore, a third chemical conversion coating 33 is disposed on the inner surface of a third bolt hole 32 in the third plated steel material 30. By disposing a chemical conversion coating on the inner surface of the bolt hole, it is possible to improve corrosion resistance against components such as moisture that enter through gaps G between the high-strength bolt and the washer and promote corrosion.

[0040] In the present disclosure, it is sufficient that a chemical conversion coating is disposed on the inner surface of at least one bolt hole, but the more bolt holes that have a chemical conversion coating disposed on their inner surface, the more the corrosion resistance of the high-strength bolt friction joint structure as a whole can be improved.

[0041] In addition, in the present embodiment, a case has been exemplified in which a chemical conversion coating is disposed on the entire inner surface of each of first bolt hole 24, second bolt hole 28, and third bolt hole 32 in each plated steel material, but the present disclosure is not limited to this. For example, in the present disclosure, a chemical conversion coating may be disposed on part of the inner surface of the bolt hole.

[0042] In addition, in the present disclosure, it is not essential that a chemical conversion coating is disposed on the inner surface of the bolt hole. In the present disclosure, for example, the chemical conversion coating may be disposed only on the joint surface without being disposed on the inner surface of the bolt hole. In addition, in the present disclosure, for example, even if blasting of the plated portion is not performed as a surface treatment for the joint surface, the "chemical conversion coating" of the present disclosure can be disposed on the inner surface of the bolt hole. In addition, in the present disclosure, the type of chemical conversion coating disposed on the inner surface of the bolt hole is not limited. In addition, the type of chemical conversion coating formed on the joint surface and the type of chemical conversion coating disposed on the inner surface of the bolt hole may be the same or different.

[0043] (gap) As shown in Fig. 3, in this embodiment, in the joint of the high-strength bolt friction joint structure 10, the gap G between the opposing surfaces of the plated steel materials at a position separated by a distance X of 5 cm from the bolt hole edge E along the radial direction of the bolt hole is 310 µm or less. The gap G (in other words, the width of the gap G) is the length measured along the thickness direction T, that is, the length measured along the up-down direction in Fig. 3. Note that in the present disclosure, the gap G is not limited to 310 µm or less and can be set arbitrarily. Also, in Fig. 4, the radial directions of the first bolt hole 24, the second bolt hole 28 and the third bolt hole 32 are parallel to the longitudinal direction L extending in the left-right direction.

[0044] In this specification, "opposing surfaces of plated steel" means "the outermost surfaces of the plated portions of the plated steel." In other words, for example, when a conversion coating such as a zinc phosphate coating is disposed on the outermost surface of the plated metal, the thickness of the conversion coating is not included in the gap. In this specification, when a conversion coating is disposed on the surface of the plated metal, the surface of the plated metal excluding the conversion coating can form the "opposing surfaces of plated steel." For example, when a blast treatment is applied to the plated portions as a surface treatment, the outermost surfaces of the plated portions can form the "opposing surfaces of plated steel."

[0045] In addition, in this embodiment, the measurement position of the gap G is exemplified as being 5 cm away from the bolt hole edge E, which corresponds to the position of the end face of the plated steel material, but this disclosure is not limited to this and can be changed as appropriate. When measuring the size of the gap G at an actual construction site, for example, the high-strength bolt friction joint structure 10 may be cut at a specific position and the gap G at the cut position may be measured. Below, the relationship between the gap G set in this embodiment and the slip coefficient after corrosion (in other words, after construction) in the high-strength bolt friction joint structure 10 that has been subjected to a surface treatment will be described using examples. EXAMPLES

[0046] (Test Example 1) First, a test example 1 will be described, which was conducted to confirm the relationship between the clearance and the distance from the bolt hole, using a high-strength bolt friction joint structure having a structure similar to the high-strength bolt friction joint structure 10 according to this embodiment. In the test example 1, a zinc phosphate coating was formed on the plated portion of the high-strength bolt friction joint structure by performing a zinc phosphate treatment as a surface treatment.

[0047] The "corroded" state in Figure 5 was formed by performing 48 cycles of accelerated corrosion testing. The accelerated corrosion testing was conducted in accordance with the "JASO M609-91 Neutral Salt Spray Cyclic Test." One cycle of the accelerated corrosion testing was performed under the following test conditions:

[0048] (Test conditions) Salt water (NaCl) spray treatment for 2 hours (salt water temperature: 35±1℃, salt water concentration: 5%) Drying process: 4 hours (drying temperature: 60±1℃, RH: 20~30%) (RH: Relative Humidity) - Wetting treatment: 2 hours (Wetting temperature: 50±1℃, RH: 95% or more)

[0049] In addition, "no corrosion" in Fig. 5 indicates a state in which the accelerated corrosion test was not performed, in other words, the number of cycles was 0. "No corrosion" corresponds to the state immediately after construction of the high-strength bolt friction joint structure.

[0050] In Test Example 1, the average gap value was calculated using the gap values ​​measured for multiple test specimens. Also, Fig. 5 shows an example of an approximation curve calculated based on the average gap values ​​obtained in the cases of "no corrosion" at 0 cycles and "corrosion" at 48 cycles.

[0051] The position of 0 (zero) on the vertical axis in Figure 5 indicates the position of the outermost surface of the plated portion. The position on the vertical axis represented by the dashed horizontal line indicates the thickness of the zinc phosphate coating formed immediately after construction. The position of 0 (zero) on the horizontal axis in Figure 5 indicates the position of the bolt hole edge. The position on the horizontal axis represented by the dashed horizontal line indicates the position of the edge of the head of the high-strength bolt immediately after construction. Figures 6(A), 6(B), and 6(C) show photographs of the high-strength bolt friction joint structure of Test Example 1, which was subjected to 48 cycles of accelerated corrosion testing.

[0052] 7(A) also illustrates an example in which, in the case of 0 cycles of "no corrosion", a gap G of approximately 217 μm is formed between the opposing surfaces of the first plated steel material 20 and the third plated steel material 30. In addition, Fig. 7(B) illustrates an example in which, in the case of 48 cycles of "corrosion", a gap G of approximately 500 μm is formed between the opposing surfaces of the first plated steel material 20 and the third plated steel material 30.

[0053] As shown in Figure 6, in both the "no corrosion" and "corrosion" cases, the greater the distance from the bolt hole, the larger the gap. Also, as can be seen by comparing the "no corrosion" case of 0 cycles with the "corrosion" case of 48 cycles shown in Figure 6, even if the distance is the same, the occurrence of corrosion causes the gap to become larger.

[0054] (Test Example 2) Next, Test Example 2, which was conducted to confirm the slip coefficient and the size of the gap of a high-strength bolt friction joint structure before and after corrosion for each type of surface treatment, will be described with reference to Tables 1 and 2 below.

[0055] [Table 1]

[0056] As shown in Table 1, the present inventors prepared high-strength bolt friction joint structures 10 for each of Examples 1 to 12 and Comparative Examples 1 to 3, and measured the slip coefficient before corrosion, the slip coefficient after corrosion, the size of the gap G before corrosion, and the size of the gap G after corrosion for each of them.

[0057] The high-strength bolt friction joint structures of Examples 1 to 12 and Comparative Examples 1 to 3 are similar to each other except for the surface treatment. Specifically, the thickness of the first plated steel material as the base material was 9 mm. The thickness of the second plated steel material and the third plated steel material as the splice plate was 2.2 mm. The width of the base material and the width of the splice plate were both 100 mm.

[0058] SS400 plated steel sheet was used as the base material, and 60k steel was used for the splice plate. The plated portion was formed by the immersion method (so-called hot-dip dipping). There was one high-strength bolt on the test side, and two high-strength bolts on the fixed side. F8T-M16 was used for all high-strength bolts. The tension of the high-strength bolts was controlled by the 120° nut rotation angle method.

[0059] Furthermore, Examples 1 to 12 and Comparative Examples 1 to 3 are divided into five groups, A to E, according to the type of surface treatment. The type of surface treatment is different for each of the groups: Examples 1 to 6, Examples 7 to 9, Examples 10 to 12, and Comparative Examples 1 to 3. Furthermore, the surface treatment of Group A of Examples 1 to 3 and the surface treatment of Group B of Examples 4 to 6 are the same zinc phosphate treatment. However, while a zinc phosphate coating is formed on the surface of the bolt hole in Group A of Examples 1 to 3, a zinc phosphate coating is not formed on the surface of the bolt hole in Group B of Examples 4 to 6.

[0060] In Table 1, "before corrosion" corresponds to the state immediately after construction of the high-strength bolted friction joint structure 10. Moreover, the "after corrosion" state was formed by carrying out 48 cycles of the accelerated corrosion test.

[0061] (Method of measuring slip coefficient) In the slip test to measure the slip coefficient in Test Example 2, a 1000 kN universal testing machine was used. The tension applied in the slip test was 94 kN. In addition, in the slip test, the tension was controlled by the value of the strain gauge embedded in the shaft of the high-strength bolt.

[0062] The slip coefficient was calculated by dividing the slip resistance by the axial force at the time of bolt tightening. For specimens in which the relative displacement (slip displacement) between the base material and the splice was 0.2 mm or less and primary slip occurred, the slip resistance of the test specimens was calculated using the load at the time the primary slip occurred. For specimens in which the slip displacement was 0.2 mm or less and primary slip did not occur, the slip resistance of the test specimens was calculated using the load at the time the relative displacement (slip displacement) between the base material and the splice reached 0.2 mm.

[0063] Table 2 below shows the minimum slip coefficient before corrosion, the minimum slip coefficient after corrosion, the difference between the minimum slip coefficient before and after corrosion, and an evaluation of the amount of drop in the minimum value for each of the five groups.

[0064] [Table 2]

[0065] As shown in Table 2, in groups A and B in which a zinc phosphate conversion coating is formed on the surface of the joint surface, the minimum slip coefficient after corrosion showed the smallest drop compared to groups C to E in which a conversion coating other than a zinc phosphate coating is formed on the surface of the joint surface. In other words, it can be seen that the effect of improving corrosion resistance by zinc phosphate treatment is the greatest among multiple chemical conversion treatments. Also, among Examples 1 to 6 included in groups A and B in which the same zinc phosphate coating is formed, it can be seen that in group B in which a zinc phosphate coating is not formed on the surface of the bolt hole, the minimum slip coefficient after corrosion showed a larger drop compared to group A in which a zinc phosphate coating is formed on the surface of the bolt hole. Specifically, as shown in Table 2, it was found that the minimum slip coefficient after corrosion showed a larger drop in the order of groups A, B, C, D, and E.

[0066] Furthermore, as shown in Table 2, in Groups A to D of the examples, the drop in slip coefficient was suppressed to 0.1 or less. On the other hand, in Group E of the comparative examples, the drop in slip coefficient after corrosion was 0.12.

[0067] In addition, Tables 1 and 2 explain the test results for the gap of the joint between the first plated steel material as the base material and the second plated steel material as the splice. In this regard, the disclosers conducted a similar test for the joint between the first plated steel material as the base material and the third plated steel material as the splice. The test results for the joint between the first plated steel material and the third plated steel material were similar to the test results explained using Tables 1 and 2 above.

[0068] Furthermore, in addition to Examples 1 to 12 and Comparative Examples 1 to 3, the present inventors prepared a plurality of surface-treated high-strength bolt friction joint structures of five groups A to E, and confirmed the slip coefficients before and after corrosion of the prepared high-strength bolt friction joint structures in the same manner as in Test Example 2. Then, as shown in Fig. 8, based on the obtained slip coefficients, a normal distribution graph was created showing the relationship between the slip coefficient and the probability density for the high-strength bolt friction joint structures of each group before and after corrosion.

[0069] In Fig. 8, the graph of the slip coefficient before corrosion for each group is shown by a solid line, and the graph of the slip coefficient after corrosion is shown by a dashed line. In addition, between the pair of graphs corresponding to each group, a horizontal arrow is shown as an example of an index of the slip coefficient drop, extending from the average slip coefficient located at the center of the peak of the graph before corrosion to the average slip coefficient located at the center of the peak of the graph after corrosion.

[0070] In addition, since the average values ​​of the slip coefficients at the peaks of the pair of graphs for Group A were almost the same, no arrow indicating the drop in the minimum value of the slip coefficient after corrosion is drawn between the pair of graphs for Group A in Figure 8. In addition, the shape of the solid line graph for Group B before corrosion was almost the same as the shape of the solid line graph for Group A before corrosion. In Figure 8, as in Table 2, it was found that the drop in the minimum value of the slip coefficient after corrosion increases in the order of Groups A, B, C, D, and E.

[0071] (Action and effect) In the high-strength bolt friction joint structure 10 according to this embodiment, a first chemical conversion coating 23 is formed on the first overlapping surface 22A and the first overlapping surface 22B of the first plated steel material 20 at the joint. Also, a second chemical conversion coating 29 is formed on the second overlapping surface 26A of the second plated steel material 26 at the joint. Also, a third chemical conversion coating 33 is formed on the third overlapping surface 30A of the third plated steel material 30 at the joint.

[0072] Furthermore, in the joint, the gap G between the opposing surfaces of the plated steel material at a position separated by a distance X of 5 cm from the bolt hole edge E along the radial direction of first bolt hole 24, second bolt hole 28, and third bolt hole 32 is 310 μm or less. Therefore, as described in the examples, it is possible to suppress a decrease in the slip coefficient after corrosion in high-strength bolted friction joint structure 10 that has been subjected to a surface treatment.

[0073] In this embodiment, a first chemical conversion coating 23 is disposed on the inner surface of first bolt hole 24. A second chemical conversion coating 29 is disposed on the inner surface of second bolt hole 28. A third chemical conversion coating 33 is disposed on the inner surface of third bolt hole 32. This makes it possible to improve the corrosion resistance of high-strength bolt friction joint structure 10.

[0074] In this embodiment, the first chemical conversion coating 23, the second chemical conversion coating 29 and the third chemical conversion coating 33 can be formed by any one of the following chemical conversion treatments: zinc phosphate treatment, blasting of the plated portion, and coating treatment with inorganic zinc-rich paint.

[0075] In this embodiment, the range of the coating weight of the zinc phosphate coating of the first chemical conversion coating 23, the second chemical conversion coating 29, and the third chemical conversion coating 33 is 1.0 g / m 2 More than 5.0g / m 2 The amount of zinc phosphate applied can be appropriately controlled according to the area of ​​the joint.

[0076] <Other embodiments> The present disclosure has been described by the above embodiment, but this description does not limit the present disclosure. It should be considered that various alternative embodiments, examples, and operation techniques will be apparent to those skilled in the art from the present disclosure. The present disclosure includes various embodiments not described above, and the technical scope of the present disclosure is determined only by the invention-specific matters in the claims that are appropriate from the above description.

[0077] <Additional Notes> The following aspects are conceptualized from this specification.

[0078] Aspect 1 is A high-strength bolt friction joint structure in which a plurality of plated steel materials having plated portions on their surfaces and bolt holes formed therein are frictionally joined by high-strength bolts, nuts, and washers, A chemical coating is formed on at least one of the joining surfaces of the plated steel material in the joining portion by surface treatment for increasing the slip coefficient, In the joint, the gap between the opposing surfaces of the plated steel material at a position 5 cm away from the bolt hole edge along the radial direction of the bolt hole is 310 μm or less. High strength bolt friction joint structure.

[0079] Aspect 2 is the conversion coating is disposed on an interior surface of at least one of the bolt holes; 2. High-strength bolt friction joint structure according to embodiment 1.

[0080] Aspect 3 is The surface treatment includes any one of a zinc phosphate treatment, a blast treatment of the plated portion, and a coating treatment of an inorganic zinc-rich paint. 3. A high-strength bolt friction joint structure according to claim 1 or 2.

[0081] Aspect 4 is The surface treatment is a zinc phosphate treatment, The coating weight of zinc phosphate as the chemical conversion coating is 1.0 g / m 2 More than 5.0g / m 2 Below is the A high-strength bolt friction joint structure according to any one of aspects 1 to 3. [Explanation of symbols]

[0082] 10 High-strength bolt friction joint structure 20 First Plated Steel (Plated Steel) 22A First overlapping surface (joint surface) 22B First overlapping surface (joint surface) 23 First chemical conversion coating 24 First bolt hole 26 Secondary plated steel (plated steel) 26A Second overlapping surface (joint surface) 28 Second bolt hole 29 Second chemical conversion coating 30 Third-coated steel (plated steel) 30A Third overlapping surface (joint surface) 32 3rd bolt hole 33 Third chemical conversion coating 34 High strength bolts 36 Nut 38 Washer E Bolt hole edge G Gap L Longitudinal T thickness direction W Width direction X Separation distance

Claims

1. A high-strength bolt friction joint structure in which a plurality of plated steel materials having plated portions on their surfaces and bolt holes formed therein are frictionally joined by high-strength bolts, nuts, and washers, A chemical conversion coating is formed on at least one of the joining surfaces of the plated steel material in the joining portion by surface treatment for increasing the slip coefficient, In the joint, a gap between the opposing surfaces of the plated steel material at a position 5 cm away from an edge of the bolt hole along a radial direction of the bolt hole is 310 μm or less. High strength bolt friction joint structure.

2. the conversion coating is disposed on an interior surface of at least one of the bolt holes; 2. A high strength bolt friction joint structure according to claim 1.

3. The surface treatment includes any one of a zinc phosphate treatment, a blast treatment of the plated portion, and a coating treatment of an inorganic zinc-rich paint.

3. A high-strength bolt friction joint structure according to claim 1 or 2.

4. The surface treatment is a zinc phosphate treatment, The amount of zinc phosphate deposited as the chemical conversion coating is 1.0 g / m 2 Above, 5.0g / m 2 Below is the A high-strength bolt friction joint structure according to claim 3.

Citation Information

Patent Citations

  • Surface treatment of metal member

    JP1983153783A

  • Steel frame junction structure and its manufacturing method

    JP2020165187A